Impacts of Gold Mining on the Social, Cultural, and Economic Structures of Kotabunan Village, East Bolaang Mongondow Regency - Faisal Ambarak; Burhan Niode; Shirley Y. V. I. Goni (Journal La Bisecoman, 2024)
One of the natural riches that our country has is gold. In managing wealth in a small way, many problems are faced. The problems that are most in the spotlight are related to the social life of communities around mining areas. This research was conducted to analyze the existence of gold mining companies in the social life of the community in Kotabunan Village, Kotabunan District, East Bolaang Mongondow Regency. The research design used is qualitative. Data was collected through interviews, observation and searching for documents related to the problem object. The research findings show that the existence of a gold mining company in Kotabunan Village, Kotabunan District, East Bolaang Mongondow Regency has brought about changes in people's lives, both positive and negative impacts which can be seen in the aspects of Social Structure, Cultural Structure and Economic Structure. Changes in Cultural Structure can be seen in changes in cultural structure. Changes in economic structure have greatly influenced people's lives, especially with the existence of corporate social responsibility (CSR) from gold mining companies, enabling people through training, basic food assistance, and changing professions as miners or managing businesses.